2005
DOI: 10.1681/asn.2004070550
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in the United States End-Stage Renal Disease Program

Abstract: 2 suicides per 100,000 patient-years, and the overall standardized incidence ratio for suicide was 1.84 (95% confidence interval, 1.50 to 2.27). In multivariable models, age >75 yr, male gender, white or Asian race, geographic region, alcohol or drug dependence, and recent hospitalization with mental illness were significant independent predictors of death as a result of suicide. Persons with ESRD are significantly more likely to commit suicide than persons in the general population. Although relatively rare, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 29 publications
3
102
0
6
Order By: Relevance
“…More recent studies show suicide to be less prevalent in contemporary ESRD populations, 24,99 although the rate is 84% higher than in the general population. 99 Alcohol dependence and hospitalization for substance abuse and mental illness were strongly associated with subsequent suicide in the ESRD population. 99 This recent study shows definitively that populations that withdraw from treatment and those that actively commit suicide represent different clinical entities, highlighting that suicide is associated with alcohol and drug dependency and the presence of mental illness.…”
Section: Withdrawal From Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies show suicide to be less prevalent in contemporary ESRD populations, 24,99 although the rate is 84% higher than in the general population. 99 Alcohol dependence and hospitalization for substance abuse and mental illness were strongly associated with subsequent suicide in the ESRD population. 99 This recent study shows definitively that populations that withdraw from treatment and those that actively commit suicide represent different clinical entities, highlighting that suicide is associated with alcohol and drug dependency and the presence of mental illness.…”
Section: Withdrawal From Dialysismentioning
confidence: 99%
“…99 Alcohol dependence and hospitalization for substance abuse and mental illness were strongly associated with subsequent suicide in the ESRD population. 99 This recent study shows definitively that populations that withdraw from treatment and those that actively commit suicide represent different clinical entities, highlighting that suicide is associated with alcohol and drug dependency and the presence of mental illness. 99 The complex relationship between depression, suicide, and withdrawal from treatment needs further clarification.…”
Section: Withdrawal From Dialysismentioning
confidence: 99%
“…Studies by Kurella et al (2005) shows that from 465,563 patients, 44,465 (9.6%) withdrew from dialysis before death and 264 (0.0005%) died from suicide in the USA. Other researchers have shown that withdrawal from dialysis occurred in 9-20% of ESRD patients and was more likely to occur in the older, white, female patients (Leggat et al, 1997;Port et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…21 In this study it was evident that the greater quantity of patients without depression was found in the period less than four years of dialysis (Table 5), which differs from the findings of some studies. 13,35,[38][39][40][41] This fact may be caused perhaps by a sense of hope in these patients that in a short time will get rid of this situation, some by the hope placed in a possible transplant 22,35,42 , others did not understand what it means to be a carrier of a chronic renal disease and its implications, then thinking that there may be a cure and that the treatment is temporary. 24 However, although the major number of patients without depression were found in the period inferior to four years of dialysis, paradoxally the most of them, among the ones that present the disorder is also found in this same period, what it is in agreement with studies previously cited.…”
Section: Erro! Indicador Não Definidomentioning
confidence: 99%